Probing cosmic velocity-density correlations with galaxy luminosity modulations - Feix, Martin (Monthly notices of the Royal Astronomical Society. Letters, 2018)
We study the possibility of using correlations between spatial modulations in the observed luminosity distribution of galaxies and the underlying density field as a cosmological probe. Considering redshift ranges, where magnification effects due to gravitational lensing may be neglected, we argue that the dipole part of such luminosity–density correlations traces the corresponding velocity–density signal which may thus be measured from a given galaxy redshift catalogue. Assuming an SDSS-like survey with mean density n¯¯¯=0.01(h−1 Mpc)−3 and effective volume Veff = 0.2(h−1 Gpc)3 at a fiducial redshift z = 0.1, we estimate that the velocity–density correlation function can be constrained with high signal-to-noise ratio ≳ 10 on scales 10–100 Mpc. Similar conclusions apply to the monopole which is sensitive to the environmental dependence of galaxy luminosities and relevant to models of galaxy formation.
Gesehen am 29.04.2020